Quantitative Finance and Fintech Research under Artificial Intelligence - Li, Runzhe (International Journal of Computer Science and Information Technology, 2024)
This paper examines the impact of artificial intelligence (AI) on quantitative finance and financial technology (fintech). It explores how AI techniques, including machine learning and deep learning, are transforming financial modeling, risk assessment, and decision-making processes. The study discusses key innovations in AI-driven fintech, such as robo-advisors and algorithmic trading. It also addresses critical challenges, including data quality issues, model interpretability, and regulatory concerns. The paper concludes by outlining future directions and ethical considerations for AI in finance, emphasizing the need for responsible development and deployment of these technologies in reshaping the financial landscape.